Photocatalytic Degradation of Humic Acid by Fe-TiO2 Supported on Spherical Activated Carbon with Enhanced Activity - Mi-Hwa Baek; Ji-Sook Hong; Ji-Won Yoon; Jeong-Kwon Suh (International Journal of Photoenergy)
Fe-TiO2 supported on spherical activated carbon (Fe-TiO2/SAC) with different Fe contents was prepared by heat treatment process after ion exchange method. The prepared Fe-TiO2/SAC was characterized by SEM, EDS, and BET. Batch experiments for photocatalytic degradation of humic acid by Fe-TiO2/SAC were carried out in the fluidized bed photoreactor. It was found that 0 wt% Fe-TiO2/SAC had high photocatalytic activity in the wavelength range of 100~280 nm. However, Fe-TiO2/SAC with Fe contents of 0.4, 0.6, and 0.8 wt% exhibited higher photocatalytic activity than 0 wt% Fe-TiO2/SAC in the wavelength range of 315~400 nm compared to that of 100~280 nm. The optimum Fe content was 0.6 wt% for maximum photocatalytic degradation of humic acid. Moreover, Fe-TiO2/SAC does not require an additional process step for separation of photocatalyst from treated water after photocatalysis.